Draft genome sequence of Acidithiobacillus thiooxidans CLST isolated from the acidic hypersaline Gorbea salt flat in northern Chile - Raquel Quatrini; Lorena V. Escudero; Ana Moya-Beltrán; Pedro A. Galleguillos; Francisco Issotta; Mauricio Acosta; Juan Pablo Cárdenas; Harold Nuñez; Karina Salinas; David S. Holmes; Cecilia Demergasso (Standards in Genomic Sciences, 2017)
Abstract Acidithiobacillus thiooxidans CLST is an extremely acidophilic gamma-proteobacteria that was isolated from the Gorbea salt flat, an acidic hypersaline environment in northern Chile. This kind of environment is considered a terrestrial analog of ancient Martian terrains and a source of new material for biotechnological applications. A. thiooxidans plays a key role in industrial bioleaching; it has the capacity of generating and maintaining acidic conditions by producing sulfuric acid and it can also remove sulfur layers from the surface of minerals, which are detrimental for their dissolution. CLST is a strain of A. thiooxidans able to tolerate moderate chloride concentrations (up to 15 g L−1 Cl−), a feature that is quite unusual in extreme acidophilic microorganisms. Basic microbiological features and genomic properties of this biotechnologically relevant strain are described in this work. The 3,974,949 bp draft genome is arranged into 40 scaffolds of 389 contigs containing 3866 protein-coding genes and 75 RNAs encoding genes. This is the first draft genome of a halotolerant A. thiooxidans strain. The release of the genome sequence of this strain improves representation of these extreme acidophilic Gram negative bacteria in public databases and strengthens the framework for further investigation of the physiological diversity and ecological function of A. thiooxidans populations.